SWITCHING AND CONCENTRATION OF ATTENTION OF CYBERSPORTSMEN OF MASS DISCHARGE - Kosmina E.A.; Makarov Yu.M.; Lutkova N.V.; Gural O.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of switching and concentration of attention among those involved in various disciplines of computer sports of mass categories. Methods and structure of the study. 175 young men from 18 to 25 years old, involved in computer sports and having sports categories from III to I, took part in the scientific work. Athletes were asked to perform five attempts each in the "attention switching" (modified Schulte tables) and "attention concentration" (modified Landolt test) exercises on the online training portal cyberten.ru developed by the authors. The mean value was calculated over five attempts. Results and conclusions. Significant differences (p<0.05) between the indicators of attention switching among athletes of the first and third sports category in the disciplines "fighting" and "sports simulator" were revealed, given the presence of a close to linear dependence on the sports category, this exercise can be included in the training. Significant differences (p<0.05) were found in the indicators of concentration of attention between those involved in "fighting", "competitive puzzles", "three-dimensional tactical combat" and "combat arena", "sports simulator", "technical simulator", "real-life strategy". time”, accompanied by a linear dependence of the increase in results from the sports category. Exercises aimed at developing concentration of attention can be recommended for training those involved in "fighting", "competitive puzzles" and "three-dimensional tactical combat".